UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA DI SEKOLAH MELALUI PENDEKATAN INKUIRI SISWA KELAS 1 SDN TUNJUNG 4 - Mega Trian Agustina; Agung Setyawan (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
This research was conducted because of the problems that occurred in grade 1 students, namely the activeness of students at school. This study aims to determine the activity of students in grade 1 using an inquiry approach or without an inquiry approach. This research method was carried out on grade 1 students at SDN Tunjung 4 Burneh. This research use desciptive qualitative approach. In this research, knowledge is built to find out and solve a problem that exists in school. This type of research used is Classroom Action Research. Based on the results that have been described that in the first cycle student activity is very less, where the acquisition of information or how to convey learning that is applied by the teacher using the lecture model, while in the second cycle students are very enthusiastic and very active in class. . So it can be concluded that the inquiry approach applied by researchers in the learning process has a very important effect on student activity, therefore, for future learning, it is more important to prioritize an effective approach for students.